Survey Evidence on the Rationality of Business Expectations: Implications from the Malaysian Agricultural Sector - Wong, Shirly Siew-Ling; Puah, Chin-Hong; Shazali, Abu Mansor (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The rational expectations hypothesis (REH) serves as an appealing mechanism in forming expectations compared to that of extrapolative or adaptive frameworks because of its consistency with the basic principles of maximizing behavior. This argument is particularly true as the basic idea of REH maintains that expectations in an uncertain world are formed under assumptions where no systematic errors and information are fully utilized. However, empirical findings from the present study showed diverse evidence of rationality in business operational forecasts formed by Malaysian agriculture firms, as capital expenditure expectations were found to be irrational but gross revenue expectations were supportive of the REH proposition. This implies that the survey of business forecasts may not work well in reflecting the true business outlook, specifically in value-related operational forecasts, which in turn would directly influence investment decisions as well as the capital budgeting process.